Methods and Applications of Data Management and Analytics - Wenjie Zhang; Zhengyi Yang (Applied Sciences)
In recent years, data management and analytics have attracted significant attention from both academia and industry, driven by the rapid growth in the volume, velocity, and variety of data generation [...]